Observation of deep near-inertial waves using PDS-CPIES in the western Arctic Ocean - Jeon, Chanhyung; Boury, Samuel; Cho, Kyoung-ho; Park, Jae-hun; Peacock, Thomas (SEANOE, 2020)
Notable spatial and temporal variability of near-inertial waves in the western Arctic Ocean is observed from direct deep current measurements. The deep current is about 50 m above the bottom. The current-meter measures a speed range of 0 to 300 cm/s with direction using an Aanderaa Data Instruments Doppler current sensor. All current data is acquired through pop-up data shuttle (PDS); AES2, AES5, AES6 : 1 year, AES3: 2 year, AES1 and AES4: no available data). After removing the four major semidiurnal tides from the current measurements, a third-order Butterworth phase-preserving band-pass filter with cutoff frequency at 0.9–1.1f is applied to extract NIW signals. Bouyancy frequency (N) is calculated from the CTD data casted from RV Araon and RV Sikuliaq.